Collaborative governance in environmental education: Systematic literature review on enhancing school-community partnerships for sustainable development - Putri Adibatur Rohmah; Ramdani Salam; Rahim Achmad (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The framework of Collaborative Governance in Environmental Education (EE) has gained increasing attention in recent years, especially in the context of sustainable development. However, the literature on this topic is still limited, so a deep understanding of how school-community partnerships can improve the effectiveness of EE programs has not been fully explained. This study aims to explore the dynamics of Collaborative Governance between schools and communities by identifying the challenges, strategies, and key outcomes that contribute to sustainable environmental education practices. Method: This study uses a Systematic Literature Review (SLR) by synthesizing empirical and conceptual findings from five relevant journal articles published between 2019 and 2025 through the Scopus database. The results of the analysis show that collaboration between schools, local governments, and civil society organizations plays an important role in fostering a culture of sustainability in the educational environment. The findings also revealed that although collaborative efforts can strengthen trust-building, joint decision-making, and mutual accountability, their implementation is still constrained by limited resources, weak coordination, and suboptimal policy support. Furthermore, this study emphasizes the importance of institutional commitment and continuous professional development for educators to maintain the sustainability of EE programs. Conclusion: The results of this study are consistent with the theory of Collaborative Governance, which emphasizes interdependence and shared responsibility among stakeholders in creating public value. This study concludes that Collaborative Governance functions not only as a coordination mechanism, but also as a transformative process that builds collective trust and empowers schools as agents of sustainable change. Novelty/Originality of this article: This study contributes through a systematic mapping of the intersection between Collaborative Governance and Environmental Education, and offers integrative conceptual insights that support the development of a Collaborative Environmental Education Framework that is aligned with Sustainable Development Goals (SDGs) points 4 and 13.